Knowledge on diabetes and its related factors among the people with type 2 diabetes in Thailand: a cross-sectional study - Nitikorn Phoosuwan; Passakorn Ongarj; Katarina Hjelm (BMC, 2022)
Abstract Background Type 2 diabetes mellitus (T2DM) is a global public health problem with complications related to knowledge guiding self-care. Limited knowledge might result in poor control of blood glucose, but there is no previous investigation measuring diabetes knowledge in people diagnosed with T2DM in Thailand. This study was aimed to investigate level of diabetes knowledge and related factors among people with T2DM in Thailand. Method This cross-sectional study was conducted in a Northeastern province in Thailand among 276 people with T2DM, 195 women and 81 men, using a standardized self-report questionnaire, the Diabetes Knowledge Test. The data were analyzed using Pearson's chi-square test, one-way analysis of variance, and independent samples t-test. Results The majority of respondents had poor diabetes knowledge in all subscales; total knowledge of diabetes (96.7%), general knowledge of diabetes (71.7%), and insulin use knowledge (92.3%). There was no difference found in knowledge scores between males and females. Having finished secondary school education or higher, being employed, or having diabetes-related complications were related to increased total diabetes knowledge and general diabetes knowledge. Conclusion The people with T2DM had poor diabetes knowledge, and those using insulin also had poor knowledge about the use of insulin.